Pengelolaan Pendidik dan Tenaga Kependidikan di SMA Al Islam 1 Surakarta - Hartono, Muh. El-Basyari; Hardini , Azizah Dwi (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine the management of educators and education at SMA Al-Islam 1 Surakarta. This study used qualitative research methods with data collection techniques that included interviews and documentation. The results showed that the management of educators and education personnel has a very large influence on the success of education and is a very important part of overall activities in schools. The management of educators and education personnel at SMA Al Islam 1 Surakarta has been running well as evidenced by the planning carried out by analyzing the needs of educators and education personnel needed. Recruitment carried out by SMA Al Islam 1 Surakarta with the dissemination of vacancy information via WhatsApp and selection carried out by the school (qualifications, interviews and microteaching) and the Foundation. For training and coaching of educators and education staff, it is carried out annually in the form of soft skills training, every week in the form of routine recitation and scheduled training from Dapodik. The promotion was carried out directly by the foundation, while the transfer was caused by personal reasons and became a State Civil Apparatus (ASN) then for dismissal at SMA Al Islam 1 Surakarta had never existed.